2013
DOI: 10.1121/1.4789939
|View full text |Cite
|
Sign up to set email alerts
|

Auditory masking patterns in bottlenose dolphins (Tursiops truncatus) with natural, anthropogenic, and synthesized noise

Abstract: Auditory masking occurs when one sound (usually called noise) interferes with the detection, discrimination, or recognition of another sound (usually called the signal). This interference can lead to detriments in a listener's ability to communicate, forage, and navigate. Most studies of auditory masking in marine mammals have been limited to detection thresholds of pure tones in Gaussian noise. Environmental noise marine mammals encounter is often more complex. In the current study, detection thresholds were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 31 publications
0
42
1
Order By: Relevance
“…This result in grasshoppers, thus, contrasts with those reported here and elsewhere (Schwartz et al, 2013) for gray treefrogs. Behavioral studies of fish (Fay, 2011), birds (e.g., Klump and Langemann, 1995;Jensen, 2007), and dolphins (Branstetter and Finneran, 2008;Trickey et al, 2010;Branstetter et al, 2013) have shown that thresholds for detecting simple acoustic stimuli (e.g., tones and narrowband noises) are lower in the presence of temporally fluctuating noises compared with unmodulated noises. The importance of these findings in relation to perceiving acoustic communication signals remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This result in grasshoppers, thus, contrasts with those reported here and elsewhere (Schwartz et al, 2013) for gray treefrogs. Behavioral studies of fish (Fay, 2011), birds (e.g., Klump and Langemann, 1995;Jensen, 2007), and dolphins (Branstetter and Finneran, 2008;Trickey et al, 2010;Branstetter et al, 2013) have shown that thresholds for detecting simple acoustic stimuli (e.g., tones and narrowband noises) are lower in the presence of temporally fluctuating noises compared with unmodulated noises. The importance of these findings in relation to perceiving acoustic communication signals remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying CMR in dolphins and other animals are related to the auditory system's ability to extract, compare, and group information from multiple auditory filters that share a common AM pattern. The addition of a tone in an auditory filter apparently decorrelates and disrupts the across-channel grouping, providing evidence that a signal is present, even for relatively low signal levels (Richards, 1987;Branstetter et al, 2013). As a result, time-domain noise metrics are needed to describe and predict auditory masking from different noise types.…”
Section: Introductionmentioning
confidence: 98%
“…The accuracy of CRs in predicting masked tonal thresholds in environmental noise is limited, primarily because CRs assume that the noise is Gaussian (G) and that masking is limited to a narrow band of noise centered on a signal's frequency (Branstetter and Finneran, 2008). In non-G noise, critical ratios for a 10 kHz tone have been shown to vary by as much as 22 dB (Branstetter et al, 2013). Accuracy in predicting masked thresholds from noise spectral density measurements is limited due to the inherent discarding of time-domain information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To predict masking in real environments, ambient and anthropogenic noise conditions in either medium can be assessed relative to measured absolute audiograms and CRs. Such an analysis provides a good (conservative) approximation for understanding the effects of noise on hearing (see Dooling et al, 2013), but does not consider the potential for masking release due to complex stimulus features (Branstetter et al, 2013). To accurately quantify the extent of masking experienced by seals exposed to realistic noise sources, more data about auditory performance under different signal and noise scenarios are required (Cunningham et al, 2014).…”
Section: Auditory Maskingmentioning
confidence: 99%